From Rotation to Growth: Understanding the Psychological and Competence Benefitsfor School Principals - Syahroni, Mashud; Hananto, Ipung; Purnama, Yunus (JURNAL AL-TANZIM, 2025)
Principals, as leaders and managers, often undergo rotation and transfer to maintain organizational efficiency. Although the impact of principal turnover on teachers and education staff has been extensively researched, the effect of rotation and transfer on principals remains largely unknown. This study aims to investigate the direct and indirect impacts experienced by principals, particularly in terms of their psychological aspects and leadership competencies. This study used a qualitative case study approach. Data collection methods included in-depth interviews and documentation studies. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that principal rotation and transfer have a positive impact on the principal's psychological well-being and competency. Psychological impacts include increased motivation and work enthusiasm, which in turn improve work quality. Meanwhile, competency impacts include improvements and positive developments in four principal competencies: personality, managerial, supervisory, and social competencies. The implications of this study suggest that principal rotation and transfer can be an effective leadership development strategy to improve the quality of education in schools. Furthermore, it is important to consider psychological aspects and competencies in every decision regarding principal turnover.